Analysis of Financial Performance Differences Before and After the Merger of Companies Listed on the Indonesian Stock Exchange - Dewi Kusumowati; Ibrahim Ibrahim (University of Merdeka Malang, 2022)
This study aims to analyze the differences in the company's financial performance before and after the merger in companies that carry out merger activities. Company performance is measured using financial ratios: Current Ratio (CR), Debt to Asset Ratio (DAR) Debt to Equity Ratio (DER), Net Profit Margin (NPM). Return On Assets (ROA), Return On Equity (ROE). This research was conducted using a quantitative method, by taking data from all public companies that merged on the Indonesia Stock Exchange (IDX) with a time span between 2014-2020, the sampling in this study used the purposive sampling method, with data obtained as many as 30 companies. who did the merger. The descriptive statistical test used is the Independent Sample T-test and the Paired Sample T-test to answer the hypothesis. The results of this study indicate that in partial testing that the current ratio shows a significant difference in the overall comparison before and after the merger. while the five financial ratios, namely DAR, DER, NPM, ROA, and ROE showed no difference three years before and three years after the merger